Peran Sosialisasi Interaktif HAM Dalam Membangun Kesadaran Anti-Diskriminasi Pada Anggota Osis MTS Kifayatul Achyar - Zakiyah Nasution; Raisa Agnia; Hani Sri Handayani; Garri Selastiani; Zulfi Ashari (Yayasan Al-Afif, 2025)
This research analyzes the role of interactive Human Rights (HR) socialization in fostering anti-discrimination awareness among OSIS members at MTs Kifayatul Achyar. As role models and the frontline against bullying, OSIS involvement is vital. Utilizing a descriptive qualitative approach with 30 participants based on experiential learning, the study found that the socialization created an effective participatory space. However, it revealed two literacy gaps. First, an ethical gap regarding the dilemma between retaliation and self-defense, risking a cycle of symbolic violence. Second, a legal literacy gap concerning the Child Criminal Justice System (SPPA) and bullying sanctions. The interactive sessions bridged these gaps by providing ethical-psychological clarification and juridical reinforcement based on the SPPA's diversion principle. Ultimately, this dialogical approach proves effective in strengthening HR awareness and preparing OSIS members as competent peer educators.